RASIO NILAI RENDAMEN dan LAMA EKSTRAKSI MASERAT ETANOL DAGING BUAH BURAHOL (Stelecocharpus burahol) BERDASARKAN CARA PREPARASI SIMPLISIA - Asni Amin (PHARMACY UMI JOURNAL SYSTEM, 2023)
Introduction : Burahol fruit (Stelecocharpus burahol) is classified as a drupa fruit with thick, fibrous flesh, in Indonesia the fruit is used by the daughters of the Yogyakarta and Surakarta palaces as a deodorant for body odor and bad breath. In order to be extracted, proper simplicia preparation techniques are needed. The purpose of this study is to compare the yield values and the duration of the burahol pulp extraction process based on the simplicia preparation method. Research methods is a laboratory experiment. The simplicia was prepared in two ways, namely the wet preparation method (wet simplicia/SB), and the simplicia drying method (dry simplicia/SK) from burahol fruit flesh (DBB). Extraction of each simplicia using ethanol solvent with maceration method. Each liquid macerate (SB and SK) was evaporated to obtain a thick extract, and the yield value was calculated.Research result : the yield value of DBB extract for SB was 11.72%, and SK was 23.408%. The time for DBB extraction by maceration for SB was longer with 9 times remaceration, while for SK it was 6 times remaceration. Conclusion: the yield value of the extract from SK is higher than that of SB